Teacher Strategies to Foster Autonomous Writing Skills in Elementary English Classes in the Digital Era - Maya Marsevani; Serina Serina; Pandu Prasodjo (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study investigates how elementary school English teachers in Batam foster students’ autonomous writing skills in the digital era. While technology offers abundant resources, young learners often depend excessively on teacher guidance or online materials, highlighting the need for effective autonomy-supportive strategies. Using a qualitative design, data were collected from four English teachers through semi-structured and written interviews, then analyzed thematically. The findings show that teachers promote writing independence through scaffolding techniques such as structured planning, guided feedback, and reflective self-evaluation. They also cultivate metacognitive awareness to help students identify and resolve their own writing difficulties. However, limited classroom technology use and varying student motivation levels remain obstacles to developing autonomy. This study contributes to the growing literature on learner autonomy in EFL primary education by demonstrating how adaptive pedagogy can balance digital integration with self-directed learning. The results underscore the importance of reflective, flexible teaching practices that prepare students for independent writing in technology-mediated contexts.